2008
DOI: 10.1123/pes.20.3.333
|View full text |Cite
|
Sign up to set email alerts
|

Use of Session Rating of Perceived Exertion for Monitoring Resistance Exercise in Children Who Are Overweight or Obese

Abstract: The purpose of this study was to investigate the use of the OMNI Resistance Exercise scale (OMNI-RES) for monitoring the intensity of different modes of resistance training in children who are overweight or obese. Sixty-one children (mean age = 9.7 +/- 1.4 years) performed three resistance training sessions every week for 4 weeks. Each session consisted of three sets of 3-15 repetitions of eight different resistance exercises. OMNI-RES RPE measures (0-10) were obtained following each set and following the end … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0
4

Year Published

2013
2013
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 20 publications
2
23
0
4
Order By: Relevance
“…Higher post-set RPE did not seem to influence the SRPE when work rate was controlled, as indicated by the lack of significant difference in SRPE between protocols matched for work rate. These findings are consistent with previous studies indicating SRPE estimations and acute RPE responses that averaged across time do not correspond and provide different information (15,23). This is logical because of the intermittent nature of effort during resistance training.…”
Section: Discussionsupporting
confidence: 93%
“…Higher post-set RPE did not seem to influence the SRPE when work rate was controlled, as indicated by the lack of significant difference in SRPE between protocols matched for work rate. These findings are consistent with previous studies indicating SRPE estimations and acute RPE responses that averaged across time do not correspond and provide different information (15,23). This is logical because of the intermittent nature of effort during resistance training.…”
Section: Discussionsupporting
confidence: 93%
“…Even so, higher SRPE did correspond with higher postset RPE in both studies and corroborates previous research, which concluded that average RPE and SRPE are complimentary measures (4). Still, interpreting the influence of postset RPE on SRPE should be done with caution as previous research has noted that average acute RPE and SRPE are not identical measures and that SRPE seems to provide different (17,24) (or perhaps additional) information.…”
Section: Discussionsupporting
confidence: 89%
“…In overweight and obese children, McGuigan et al [23] identified no significant difference between the session RPE and traditional RPE. Sweet et al [15] found consistent results between the session RPE used for aerobic exercise and that used for weight training.…”
Section: Discussionmentioning
confidence: 99%